2020
DOI: 10.1371/journal.pone.0240400
|View full text |Cite
|
Sign up to set email alerts
|

In-hospital mortality is associated with inflammatory response in NAFLD patients admitted for COVID-19

Abstract: Background & aims Although metabolic risk factors are associated with more severe COVID-19, there is little evidence on outcomes in patients with non-alcoholic fatty liver disease (NAFLD). We here describe the clinical characteristics and outcomes of NAFLD patients in a cohort hospitalised for COVID-19. Methods This study included all consecutive patients admitted for COVID-19 between February and April 2020 at Imperial College Healthcare NHS Trust, with either imaging of the liver available dated within one y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(90 citation statements)
references
References 25 publications
2
84
1
Order By: Relevance
“…The fact that males with no underlying comorbidity or disease also tend to have higher death risk than females as age progresses also reinforces the findings of an asymmetric impact of COVID-19 in regards to sex and is consistent with previous studies' results [1][2][3][4][5]. A possible explanation provided in [5], regarding male infectiousness, relates to smoking and higher circulating angiotensin converting enzyme 2 (ACE2) levels in men, SARS-CoV-2 utilizes ACE2 receptors found at the surface of the host cells to get inside the cell, this is also an important factor in specific underlying comorbidities or diseases.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The fact that males with no underlying comorbidity or disease also tend to have higher death risk than females as age progresses also reinforces the findings of an asymmetric impact of COVID-19 in regards to sex and is consistent with previous studies' results [1][2][3][4][5]. A possible explanation provided in [5], regarding male infectiousness, relates to smoking and higher circulating angiotensin converting enzyme 2 (ACE2) levels in men, SARS-CoV-2 utilizes ACE2 receptors found at the surface of the host cells to get inside the cell, this is also an important factor in specific underlying comorbidities or diseases.…”
Section: Discussionsupporting
confidence: 91%
“…When dealing with an epidemiological scenario, the profiling of death probabilities, conditional on subjects' features, can help identify risk groups and guide response strategies. In this context, when dealing with the assessment of death probability profiles, the target is binary, with 0 labeling a person who survived and 1 a person who died 3 .…”
Section: Probability Prediction Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven of the included articles reported cohort studies [ 11 , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] ], while three were case-control or cross-sectional analysis [ [32] , [33] , [34] ]. The majority of the studies were from Asia (seven, in China) [ 11 , 24 , 26 , 27 , [29] , [30] , [31] ], while four were from the USA [ 22 , 23 , 25 , 28 ], and one from the UK [ 33 ], Mexico [ 32 ], and Israel [ 34 ] each. The studies were conducted in the time frame between December 2019 to September 2020.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies confirmed the NAFLD as per imaging based on ultrasound or computerized tomography (CT) [ 23 , 24 , 27 , 30 , 33 ], four studies as per the hepatic steatosis index (HIS) [ 11 , 22 , 26 , 32 ], three used consensus definition of MAFLD [ 29 , 31 , 34 ] and two as per International Classification of Diseases (ICD) [ 25 , 28 ] code. Obesity, hypertension, type 2 diabetes mellitus (T2DM), and dyslipidemia were the major co-morbidities reported across the included studies with a higher prevalence in the NAFLD cohort [ [22] , [23] , [24] , [25] , [26] , [28] , [29] , [30] , [31] , [32] , [33] ]. Other co-morbidities included cardiovascular diseases (CVD), lung disease, and metabolic dysregulation [ 23 , 26 , 28 , [31] , [32] , [33] ].…”
Section: Resultsmentioning
confidence: 99%